KEPENTINGAN UMUM DALAM PERLINDUNGAN PATEN - Winner Sitorus (Yuridika, 2014)
This article aimed at studying provisions in TRIPs Agreement and Law Number 14 of 2001 regarding Patent, particularly provisions reflecting criteria of public interest.The approach used is statutory and conceptual approaches by analysing TRIPs Agreement and Law Number 14 of 2001. It is concluded that public interest has been stipulated generally in TRIPs Agreement and Law Number 14 of 2001 in their provisions regarding kind and scope of the use of limitation and exception of patent holder’s exclusive rights. Law Number 14 of 2001 basically has implemented limitation and exception provisions stipulated in TRIPs Agreement. However, it does not provide further and clearer elaborations on some provisions that need to be elaborated further. In addition, both TRIPs Agreement and Law Number 14 of 2001 do not provide criteria as to public interest.Keywords: public interest, criteria, exception, limitation, patent.